A novel surgical approach for hypopharyngeal carcinoma resection via the paraglottic space - Li, Wenming (BMC Surg, 2021)
BACKGROUND: Conservative surgery has proven advantageous in controlling hypopharyngeal squamous cell carcinoma (HSCC) and preserving speech and swallowing function in carefully selected patients, typically with early T-stages diseases. A variety of modified surgical procedures or techniques have been proposed. METHODS: In this study, we present a novel surgical approach for hypopharyngeal carcinoma resection utilizing the paraglottic space. RESULTS: The paraglottic space approach can help expose neoplasms under direct vision and save mucosa during surgery while sufficiently preserving laryngeal function, thus benefiting postoperative swallowing and reducing complications. A large cohort of 426 patients with HSCC underwent surgical treatment at our institution using this approach, demonstrating an overall survival (OS) rate of 52.3% and low incidences of postoperative complications. CONCLUSIONS: This surgical approach can be applied in patients with the lesions that do not involve the paraglottic space. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12893-021-01223-1.